Representasi Kehidupan Ideal dan Tekanan Sosial di Instagram: terhadap Strategi Pencitraan Diri Dikalangan Anak Muda - Santoso, Bagus; Pratiwi, Tria; Damayanti, Elisa; Manurung, Afwan Syahril (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study addresses the phenomenon of representation of ideal life and social pressure on Instagram as well as its impact on self-image strategies among adolescents. The research background is based on the increasing use of social media as a space of digital identity formation that almost features an engineered and curated image of life. This study uses qualitative methods with a descriptive approach to describe in depth the dynamics of self-image that arise as a result of social pressures in interactions in digital spaces. Data sources were obtained from literature reviews that included scholarly journals, books, and articles related to self-image theory, social media, as well as digital identity. The data collection technique was conducted through non-participant observation of the youth’s uploads and interactions on Instagram. Data analysis used Klaus Krippendorff’s content analysis approach which allowed for a systematic interpretation of texts, images, and symbols representing ideal lives as well as self-image strategies. To ensure validity, a source triangulation technique was used testing the consistency of data between observations and scientific literature. The results of the study suggest that representations of ideal lives on Instagram play a role as social standards that create psychological pressure and encourage adolescents to strategically adjust their identities. Discussion shows that self-image on Instagram is performative, reflective, and loaded with symbolic value that is influenced by algorithmic logics and social expectations. In conclusion, Instagram has been a space of hyperreality that influences young people’s identity construction through its complex, adaptive, and simultaneously problematic visual imagery, Instagram.